PIAS1 and STAT‐3 impair the tumoricidal potential of IFN‐γ‐stimulated mouse dendritic cells generated with IL‐15. Issue 8 (23rd May 2014) - Hanke, Neale T.; LaCasse, Collin J.; Larmonier, Claire B.; Alizadeh, Darya; Trad, Malika; Janikashvili, Nona; Bonnotte, Bernard; Katsanis, Emmanuel; Larmonier, Nicolas
<x xml:space="preserve">Abstract</x> Primarily defined by their antigen‐presenting property, dendritic cells (DCs) are being implemented as cancer vaccines in immunotherapeutic interventions. DCs can also function as direct tumor cell killers. How DC cytotoxic activity can be efficiently harnessed and the mechanisms controlling this nonconventional property are not fully understood. We report here that the tumoricidal potential of mouse DCs generated from myeloid precursors with GM‐CSF and IL‐15 (IL‐15 DCs) can be triggered with the Toll‐like receptor (TLR) 4 ligand lipopolysaccharide to a similar extent compared with that of their counterparts, conventionally generated with IL‐4 (IL‐4 DCs). The mechanism of tumor cell killing depends on the induction of iNOS expression by DCs. In contrast, interferon (IFN)‐γ induces the cytotoxic activity of IL‐4 but not IL‐15 DCs. Although the IFN‐γ‐STAT‐1 signaling pathway is overall functional in IL‐15 DCs, IFN‐γ fails to induce iNOS expression in these cells. iNOS expression is negatively controlled in IFN‐γ‐stimulated IL‐15 DCs by the cooperation between the E3 SUMO ligase PIAS1 and STAT‐3, and can be partially restored with PIAS1 siRNA and STAT‐3 inhibitors.